Thoughts and opinions about fertility preservation and family building from the transgender community—an interview-based approachAJOG Global Reports at a Glance - Zachary W. Walker, MD; Katelin McDilda, MD; Andrea Lanes, PhD; Randi Goldman, MD, MBA; Elizabeth S. Ginsburg, MD; Iris Insogna, MD (AJOG Global Reports)
Background: When considering the significant prevalence of transgender and gender nonconforming individuals, it is imperative that physicians work to understand the unique needs of this population including paths to family building and fertility preservation. Objective: To understand the thoughts and opinions about fertility preservation and family building within the transgender community. Study design: Survey-based study and qualitative study at a single, large hospital-affiliated fertility center. A 16-question survey followed by a 30-minute virtual interview was utilized. Forty-three participants completed the survey and were used for quantitative analysis, and 40 audio files were used for qualitative analysis. Results: The average age of participants was 27.0±7.3 years old. The majority of participants were assigned female at birth (70.7%); however, most participants’ gender identities were transgender (54.8%) or nonbinary (47.6%). The average age at which participants realized they were transgender and disclosed their identity to a friend, or partner, was 16.2±7.0 (range 3–30) and 20.1±5.6 (range 11–33), respectively. The average age that participants disclosed their gender identity to their parents, siblings, or other family was 22.4±5.9 (range 12–35). Five categories were utilized to summarize the experiences and opinions of the participants: family building and parenthood goals, influences of family background/partner on parenthood goals, awareness and knowledge about fertility preservation, barrier to family building, and recommended healthcare provider communication and education. Sixteen participants (40.0%, n/N=16/40) were interested in having children in the future, 18 (45.0%, n/N=18/40) were unsure/dependent on their partner, and 6 (15.0%, n/N=6/40) were not interested in having children. Of those interested in having children (n/N=16/40), the majority wished to utilize adoption to build their family (68.8%, n/N=11/16). Nine participants (22.5%, n/N=9/40) reported that fertility preservation was never discussed. Most participants agreed that gender dysphoria, cost, inadequate counseling, and improvements in healthcare knowledge about transgender individuals were key influences on their opinions about pursuing fertility preservation or parenthood. Conclusion: Transgender individuals want to build families, and the majority consider adoption the preferred method. There are still transgender individuals who are not counseled about fertility preservation. It is imperative the healthcare system continues to improve the education of healthcare providers about management and care of transgender individuals to provide the best care for this vulnerable population.